Early spears as thrusting weapons: Isolating force and impact velocities in human performance trials. (December 2016) - Milks, Annemieke; Champion, Stephen; Cowper, Elizabeth; Pope, Matt; Carr, Debra
Abstract: Human hunting has been a cornerstone of research in human evolutionary studies, and decades worth of research programmes into early weapon systems have improved our understanding of the subsistence behaviours of our genus. Thrusting spears are potentially one of the earliest hunting weapons to be manufactured and used by humans. However, a dearth of data on the mechanics of thrusting spear use has hampered experimental research. This paper presents a human performance trial using military personnel trained in bayonet use. Participants thrusted replicas of Middle Pleistocene wooden spears into PermaGel™. For each spear thrust, impact velocity was recorded with high-speed video equipment, and force profiles were recorded using a force transducer. The results demonstrate that training improves performance when compared with previous experimental results using untrained participants, and that the mechanics and biomechanics of spear thrusting are complex. The trial confirms that previous spear thrusting experiments firing spears as projectiles are failing to replicate the entire spear thrusting event, and that crossbows are too powerful to replicate the low velocities involved in spear thrusting. In order to better understand evidence of spear thrusting in the archaeological record, experimental protocols accurately replicating and recording the mechanics of spear thrusting in the past are proposed. Highlights: We conduct a human performance trial in two-handed spear thrusting. We record depth of penetration into PermaGel™, impact velocity and force. The mechanics and biomechanics of two-handed spear thrusting are complex. Spear thrusting is best replicated using trained human participants. The results provide key human performance data for future experimental replication.